PENYELESAIAN HUTANG KREDIT ANTARA KOPERASI KARYAWAN PT. PLN (PERSERO) CABANG BINJAI DENGAN ANGGOTA KOPERASI KARYAWAN YANG TELAH PENSIUN - TIESA SALEH (PREMISE LAW JURNAL, 2017)
One of the types of default committed by cooperative members at the Employee Cooperative of PT. PLN (Persero), Binjai Branch, is the breach of paying off their credit, its interest, and owed administrative cost. It is called default when one commits prohibited act in a contract. The employees who have been retired at PT. PLN (Persero), Binjai Branch, can become extraordinary members of the cooperative. Default committed by retired employees will harm the cooperative, but the cooperative usually finds difficulty in suing for compensation.